1994
DOI: 10.1093/bja/73.6.847
|View full text |Cite
|
Sign up to set email alerts
|

A brief historical review of non-anaesthetic causes of fires and explosions in the operating room

Abstract: Fires and explosions have occurred in the operating theatre for many years. Flammable inhalation anaesthetic agents were responsible for many incidents in the past, but these are no longer available in many countries. Other causes of fires and explosions still exist in the operating theatre and, from time to time, result in serious and occasionally fatal injury. Flammable gastrointestinal gases have been the cause of injury to patients during gastric surgery, laparoscopy and during examination of the large bow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
0
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(52 citation statements)
references
References 62 publications
(67 reference statements)
1
47
0
4
Order By: Relevance
“…First, it has been recommended that [1] 10% povidone-iodine in alcohol solution, [2] thimerosal in 50% alcohol solution, [3] 70% chlorhexidine hand rub, and [4] methanol or ethanol should not be used for skin cleaning in the operative field. Second, when using electro-surgical equipment, minimize the time it is used and use non-flammable equipment instead of flammable equipment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, it has been recommended that [1] 10% povidone-iodine in alcohol solution, [2] thimerosal in 50% alcohol solution, [3] 70% chlorhexidine hand rub, and [4] methanol or ethanol should not be used for skin cleaning in the operative field. Second, when using electro-surgical equipment, minimize the time it is used and use non-flammable equipment instead of flammable equipment.…”
Section: Discussionmentioning
confidence: 99%
“…[1] Operating room fires and burns are relatively rare, but such disasters can complicate almost any surgical procedure. In the United States, approximately 100 operating room fires are reported each year, although burns to the patient are not counted.…”
mentioning
confidence: 99%
“…Fire risks, through the ignition of tubing, some anaesthetic gases or chemicals (eg alcoholic disinfectants), should be identifi ed and avoided. [26][27][28][29][30] In addition, the products of tissue ablation (plume) represent a considerable hazard that can affect the clinician, auxiliary personnel and the patient. Suitable fi ne mesh face masks specifi c to surgical laser use, gloves and high-speed suction aspiration must be used to control the spread of all laser tissue ablation products (see Fig.…”
Section: Non-beam Risksmentioning
confidence: 99%
“…In ophthalmic practice the incidence of surgical fires reported is very rare despite the presence of oxygen and the use of electrocautery [12].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies have shown that hot wire cautery or diathermy generates enough heat to ignite all alcohol based antiseptics even if these contain as little as 20% alcohol [3]. Fuels are abundant in the operative field that include prep solutions, drapes, sponges, endotracheal tubes, petroleum based ointments, tinctures, as well as many others [12]. In the presence of a high oxygen environment, all of these substances can burst into flames and burn intensely.…”
mentioning
confidence: 99%